Empowering Women and Families in Early Detection of Hypertension Complications in Pregnancy - Rasyid, Puspita Sukmawaty; Podungge, Yusni; Olii, Nancy; Noor, Hajah Salmah Haji Mohd (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Hypertension is the main cause of death for pregnant women, which is 31,90% in 2022. Early detection of hypertension complications tends to be actively carried out by health workers rather than empowering mothers, husbands, and families. This study aims to identify the differences in knowledge and attitudes of pregnant women regarding the early detection of hypertensive complications and the role of family support in hypertension prevention, before and after receiving intervention through the use of booklets. This quasi-experimental study used a one-group pretest-posttest design with 60 hypertensive pregnant women. Participants completed questionnaires measuring knowledge and attitudes about hypertension. After receiving a hypertension booklet to read for three days, follow-up evaluations were conducted on family support (day 10), early detection of complications, and blood pressure (day 14). Data were analyzed using paired sample tests. The research results show that the knowledge significantly improved after the intervention (mean increase of 2.47, p=0.000), while no significant change was found in attitudes (p=0.214). Family support roles increased significantly (mean increase of 2.02, p=0.000). Additionally, 88.3% of respondents could detect early hypertension complications, and 81.7% had normal blood pressure after the intervention. The conclusion is there are differences in the knowledge of pregnant women and the role of family in the prevention of pregnancy hypertension before and after receiving the booklet intervention. There is no difference in the attitude of pregnant women before and after receiving the booklet intervention. Suggestions for researchers further need to formulate strategies related to early detection of pregnancy hypertension starting from the family level by involving a network of cooperation between the government and community organizations to prioritize health education at the family level.